Enhancing social experience in smart stadium with Wi-Fi 6 quality management - Zakaria, Nurul Azma; Rosman, Muhammad Harith Hakim; Hamid, Erman; Jafar, Fairul Azni; Abbas, Wan Faezah; Mohamad Nazir, Muhammad Rahmatur Rahman (Research and Scientific Innovation Society, 2025)
Smart stadiums are revolutionizing live sports by creating digitally connected environments that turn spectators into active participants. However, when thousands of fans simultaneously use public Wi-Fi for streaming and sharing, network congestion often occurs. This overload degrades connectivity and disrupts live broadcasts for remote viewers, causing buffering, poor quality, and interruptions. Limited bandwidth and diverse user demands further challenge Wi-Fi performance, leading to inconsistent experiences. This study proposes a Wi-Fi 6-based Quality of Service (QoS) management framework to ensure uninterrupted, high-quality video streaming during live events. Developed using Python and NS-3 simulation tools, the framework employs the Priority Queuing algorithm to optimize traffic flow. Agile methodology guided iterative development for scalability and adaptability. Performance was evaluated under simulated high-density conditions using key QoS metrics: throughput, packet loss ratio, traffic volume, and bandwidth usage. Results show that Priority Queuing significantly reduces congestion, improves responsiveness, and supports real-time traffic optimization. the study highlights how reliable Wi-Fi 6 connectivity can enhance inclusivity, improve operational efficiency, and foster more immersive and equitable social experiences. Future work will explore advanced prioritization techniques, integration with emerging technologies, and personalization based on user feedback, which bridges technical precision with meaningful social impact in the Wi-Fi 6 era.